THE EFFECT OF RICOSRE LEARNING MODEL WITH PODCAST ASSISTANTS ON SKILLS SPEAKING ON GRADE XI - Sihotang, Winri Agnes; Simaremare, Juni Agus; Sitanggang Gusar, Martua Reynhat (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This study aims to determine the effect of the RICOSRE learning model assisted by Podcast on speaking skills in debate material for class XI students of SMA Parulian 1 Medan. This study uses a quantitative experimental research method One Group Pretest-Posttest Design. The population in this study were all class XI students totaling 103. This study only used one class as a pretest and posttest class. The data analysis techniques used were normality test, homogeneity test, and hypothesis test, after which research was conducted for the pretest and posttest classes using the RICOSRE learning model assisted by podcasts, the average pretest class value was 54.93 with a standard deviation of 9.74 and the average posttest class value was 82.25 with a standard deviation of 76.50. The results of the pretest and posttest class prerequisite tests state that the sample is normally distributed and homogeneous, so the value will be consulted with the 5% significance level table with dk = (N1 + N2) -2 = 62. By looking at the ttable value, the ttable value is 5% = 1.99. Therefore, tcount> ttable (36.79> 1.99) is obtained. So it can be concluded that the HO hypothesis is rejected and the Ha hypothesis is accepted.